Undetected [compact disc, unabridged] - Henderson, Dee (Brilliance Audio, 2014)
Mark wants someone to come home to after sea patrols. The woman he has in mind is young, pretty, and very smart. She's a civilian, but she understands life in the navy. And he has a strong sense that life with her would never be boring. But she may be too deep in her work to see the potential in a relationship with him. Gina Gray would love to be married. But a breakup she didn't see coming has her focusing all her attention on what she does best, ocean research.